How is the role of SENCO understood in one primary school? - Buckley, Hannah (2016)
This research project seeks to discover how the role of the Special Educational Needs Co-ordinator (SENCO) is understood amongst staff in one primary school. Presently, there is statutory guidance on what the role of the SENCO entails and what its' key responsibilities are and I am aiming to find out if staff views in one primary school align with these. The main motivation for this study is that I am shortly taking on the role of SENCO in a primary school and want to explore the views and opinions of staff members around their understanding and knowledge of the role. This will allow me to gain an insight into their thoughts regarding the SENCO's responsibilities and allow me to compare these with national guidelines laid out in the most current Special Educational Needs and Disability Code of Practice (DfE, 2015). The study will also allow me to seek a greater understanding of the SENCO role by reviewing literature surrounding how it has changed and what the role now entails. By gaining a clearer understanding of the role of the SENCO nationally, and within this particular primary school, it will allow me to ensure that all needs of the staff are met and the 'key responsibilities' (DfE, 2015) of the SENCO are addressed when I step into the role. Furthermore, by understanding the SENCO role more thoroughly, it will allow for dissemination of what I have discovered amongst staff members and allow for good practice to be shared to promote the inclusion of children with Special Educational Needs (SEN) in school. The limitations of the research revolve around the size of the primary school that my study will take place in. The school is relatively small with limited staff numbers meaning that the scope of my study cannot be too wide and opinions and views of the staff members may not differ greatly to one another. As discussed in the Literature Review below, much of the previous work in this area has concentrated on what the Code of Practice asks for and how it has developed over the years. In this study, however, I have given attention to how the role is actually perceived by other staff members working alongside the SENCO and how thorough this understanding is.